A call for formal telemedicine training during stroke fellowship. (10th May 2016) - Jagolino, Amanda L.; Jia, Judy; Gildersleeve, Kasey; Ankrom, Christy; Cai, Chunyan; Rahbar, Mohammad; Savitz, Sean I.; Wu, Tzu-Ching
Abstract : During the 20 years since US Food and Drug Administration approval of IV tissue plasminogen activator for acute ischemic stroke, vascular neurology consultation via telemedicine has contributed to an increased frequency of IV tissue plasminogen activator administration and broadened geographic access to the drug. Nevertheless, a growing demand for acute stroke coverage persists, with the greatest disparity found in rural communities underserved by neurologists. To provide efficient and consistent acute care, formal training in telemedicine during neurovascular fellowship is warranted. Herein, we describe our experiences incorporating telestroke into the vascular neurology fellowship curriculum and propose recommendations on integrating formal telemedicine training into the Accreditation Council for Graduate Medical Education vascular neurology fellowship.